Introduction to molecular-microsimulation of colloidal dispersions - Satoh, A. (Studies in interface science, 2003)
This title provides an introduction to molecular-microsimulation methods for colloidal dispersions and is suitable for both self-study and reference. It provides the reader with a systematic understanding of the theoretical background to simulation methods, together with a wide range of practical skills for developing computational programs. Exercises are included at the end of each chapter to further assist the understanding of the subjects addressed. - Provides the reader with the theoretical background to molecular-microsimulation methods - Suitable for both self-study and reference - Aids the reader in developing programs to meet their own requirements.